Digital Financial Literacy and Customer Protection on Customer Trust with the Use of Mobile Banking as a Moderating Variable - Aisyah, Siti Nur; Wahyuni, Rizki Sri (Jurnal Ilmiah Akuntansi & Bisnis, 2025)
This research examines the effect of digital financial literacy and customer protection on customer trust, with mobile banking serving as a mediating variable. A quantitative approach was employed using a field survey of individuals aged 17 to 44 in Sukabumi who use mobile banking services. From this population, 151 respondents were selected through non-probability sampling focusing on purposive sampling to qualify the mobile banking users. Data were collected via an online questionnaire and analyzed with Smart PLS software. The findings reveal that respondents’ digital financial literacy is categorized as good and has a significant positive influence on both mobile banking usage and customer trust. Moreover, digital financial literacy positively affects customer protection. The results also show that mobile banking usage enhances customer trust, while customer protection contributes positively to mobile banking usage.In addition, the study identifies several mediated relationships: digital financial literacy affects customer trust through mobile banking usage; customer protection influences customer trust through mobile banking usage; and digital financial literacy impacts mobile banking usage through customer protection. Finally, digital financial literacy also shapes customer trust when mediated simultaneously by customer protection and mobile banking usage.